Activation-Induced Autophagy Is Preserved in CD4+ T-Cells in Familial Longevity. (9th May 2017) - Raz, Yotam; Guerrero-Ros, Ignacio; Maier, Andrea; Slagboom, P. Eline; Atzmon, Gil; Barzilai, Nir; Macian, Fernando
Abstract: As with many other tissues and organs, the immune system is also affected by age. Immunosenescence is characterized by a decreased ability of immune cells to mount a productive response upon exposure to new antigens. Several studies have reported that members of families with exceptional longevity show improved immune function, which might contribute to the increased life- and health-span observed in those families. Autophagy is a catabolic process that delivers cytoplasmic material to the lysosomes for degradation. Defective autophagy is known to be associated with age in several cell types and tissues and its dysregulation is related to age-associated diseases. In T-cells, autophagy has an essential role in modulating protein and organelle homeostasis and in the regulation of activation-induced responses. In this study, using two different cohorts of individuals belonging to families with exceptional longevity, we show that CD4 + T-cells isolated from the offspring of parents with exceptional longevity show improved activation-induced autophagic activity compared with age-matched controls. Interestingly, increased autophagy is positively correlated with increased interferon-γ production. In conclusion, autophagy appears to be better maintained in members of families with extended longevity and positively correlates with improved T-cell function.